Polarizing an antiferromagnet by optical engineering of the crystal field - Disa, AS; Fechner, M; Nova, T; Liu, B; Foerst, M; Prabhakaran, D; Radaelli, P; Cavalleri, A (Nature Research, 2020)
Strain engineering is widely used to manipulate the electronic and magnetic properties of complex materials. For example, the piezomagnetic effect provides an attractive route to control magnetism with strain. In this effect, the staggered spin structure of an antiferromagnet is decompensated by breaking the crystal field symmetry, which induces a ferrimagnetic polarization. Piezomagnetism is especially appealing because, unlike magnetostriction, it couples strain and magnetization at linear order, and allows for bi-directional control suitable for memory and spintronics applications. However, its use in functional devices has so far been hindered by the slow speed and large uniaxial strains required. Here we show that the essential features of piezomagnetism can be reproduced with optical phonons alone, which can be driven by light to large amplitudes without changing the volume and hence beyond the elastic limits of the material. We exploit nonlinear, three-phonon mixing to induce the desired crystal field distortions in the antiferromagnet CoF2. Through this effect, we generate a ferrimagnetic moment of 0.2 μB per unit cell, nearly three orders of magnitude larger than achieved with mechanical strain.